Analytical Method in Solving Flow of Viscoelastic Fluid in a Porous Converging Channel - M. Esmaeilpour; Naeem Roshan; Negar Roshan; D. D. Ganji (International Journal of Mathematics and Mathematical Sciences, 2011)
An analytical method, called homotopy perturbation method (HPM), is used to compute an approximation to the solution of the nonlinear differential equation governing the problem of two-dimensional and steady flow of a second-grade fluid in a converging channel. The table and figures are presented for influencing various parameters on the velocity field. The results compare well with those obtained by the numerical method. The method is straightforward and concise, and it can also be applied to other nonlinear evolution equations in mathematical physics.